Comparing the degradation of Poly-B-(hydroxybutyrate), poly-B-(hydroxbutyrate-co-valerate)(PHBV) and PHBV/cellulose tricate blend - Muhamad, Ida Idayu; Lee, Kar Joon; Mohd. Noor, Mohd. Azemi (Plastics and Rubber Institute of Malaysia, 2006)
The hydrolytic degradation of poly-b-(hydroxybutyrate) PHB, poly-b- (hydroxybutyrate-co-b-valerate) (PHBV) and PHBV/cellulose triacetate blend was sutnuddeire dd ifferent pH at 37 Â°C. PHBV showed a similar trend of degradation to PHB but at rhaitgehse irn alkaline medium. The presence of cellulose triacetate in the blend increased the water uptake and permeability which favoured the hydrolytic degradation especially in lpoHw mere dium. In the surface hydrolysis of PHB and its blends, the overall degradation rate was increased with higher pH values. The melting temperature, crystallinity and tensile properties were also determined. The blend, PHBV/CTAc had the lowest crystallinity values and hPaHdB t he highest. However, the blends were mechanically better in strength and toughness